Advancing institutionalization and sustainability of field epidemiology training programs in the Eastern Mediterranean region - Khader, Yousef; Al-waleedi, Ali Ahmed; Al-Shoteri, Sheikh Abdulhafed; Al Wahaibi, Adil Said; Muhammadi, Ahmad Farshid; Bashier, Haitham; Bani Mousa, Ayman; Dwekat, Ramez; Usman, Shamaila; Bin-Ghouth, Abdulla; Chrifi, Hassan; Al-Hawwash, Tareq; et al. (Frontiers in Public Health, 2025)
IntroductionSustaining Field Epidemiology Training Programs (FETPs) is critical for long-term public health capacity. Institutionalization—embedding programs within national health systems—is a major step toward sustainability. This manuscript explores the experiences, perceived challenges, and strategies related to the institutionalization, sustainability, and funding of FETPs in the Eastern Mediterranean Region (EMR) and offers recommendations to strengthen their long-term integration within national health systems.MethodsA participatory regional workshop was held in Amman from May 18–20, 2025, to review frameworks, share country experiences, and develop sustainability plans. Participants included FETP directors, ministry officials, and alumni from nine countries. Sessions addressed governance, financing, accreditation, career pathways, and stakeholder engagement. Data were synthesized thematically from session notes and program documents.ResultsTwenty-eight participants representing Afghanistan, Iraq, Jordan, Pakistan, Palestine, Tunisia, Morocco, Oman, and Yemen attended the regional workshop. Most were experienced public health professionals and FETP graduates. Country teams highlighted the importance and impact of FETP, while funding constraints and undefined career tracks were common challenges. Institutionalization, defined as embedding FETPs into national strategies with government ownership, legal frameworks, and dedicated financing, emerged as a critical priority. Participants recommended shifting to mixed financing models, pursuing accreditation, and linking programs to universities. The lack of career pathways underscore the need for policies recognizing FETP qualifications in promotions. Stakeholder engagement and advocacy were identified as essential for sustaining support.ConclusionSustaining FETPs requires deliberate country-led action, stable funding, accreditation, and clear career progression. With committed leadership and regional collaboration, FETPs can evolve into permanent pillars of public health capacity and health security.